2020
DOI: 10.1007/s10072-020-04679-w
|View full text |Cite
|
Sign up to set email alerts
|

Acutely altered mental status as the main clinical presentation of multiple strokes in critically ill patients with COVID-19

Abstract: Background and aims Cerebral infarction in COVID-19 patients might be associated with a hypercoagulable state related to a systemic inflammatory response. Its diagnosis might be challenging. We present two critically ill patients with COVID-19 who presented acutely altered mental status as the main manifestation of multiple strokes. Methods Clinical presentation and diagnostic work-up of the patients. Results Two patients in their sixties wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…That our patients were diagnosed with Covid-19 pneumonia and neurological disease after presenting to the emergency room suggests the neurological presentation of Covid-19. Acute change in consciousness, which was the most common complaint in our study, may be an ischaemic stroke symptom in severe Covid-19 cases [27] . Hypercoagulopathy is the cause of cerebrovascular diseases pathogenesis in Covid-19.…”
Section: Discussionmentioning
confidence: 51%
“…That our patients were diagnosed with Covid-19 pneumonia and neurological disease after presenting to the emergency room suggests the neurological presentation of Covid-19. Acute change in consciousness, which was the most common complaint in our study, may be an ischaemic stroke symptom in severe Covid-19 cases [27] . Hypercoagulopathy is the cause of cerebrovascular diseases pathogenesis in Covid-19.…”
Section: Discussionmentioning
confidence: 51%
“…5 Hypercoagulation during SARS-CoV-2 infection has been linked to cerebral embolism in several cases. 6,7 In our case, the patient was asymptomatic, and therefore, the duration of infection remains unknown. However, a second test performed 7 days after the positive one was already negative, thus suggesting that infection occurred earlier.…”
Section: Discussionmentioning
confidence: 78%
“… 5 Hypercoagulation during SARS-CoV-2 infection has been linked to cerebral embolism in several cases. (6) , (7) …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and severity of these psychiatric symptoms, attention deficits, and hyperactivity symptoms increased the risk for problematic internet use during the COVID-19 pandemic [ 51 ]. Moreover, a case series reported that critically ill COVID-19 patients with multiple acute bilateral ischemic lesions exhibited alterations of mental status but no neurological deficits [ 52 ]. A group of experts convened by the UK Academy of Medical Sciences and the mental health research charity also advocate monitoring and evaluating brain function, and mental health issues such as anxiety, depression, insomnia, self-harm, and suicide in COVID-19 patients and related vulnerable populations [ 53 ].…”
Section: The Presence and Prevalence Of Neuropsychiatric Manifestations In Covid-19 Patientsmentioning
confidence: 99%